2020
DOI: 10.1097/gox.0000000000003163
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Preparedness in Plastic Surgery Residency Training

Abstract: Background: Graduating competent surgical residents requires progressive independence during training. Recent studies in other surgical subspecialties have demonstrated overall fewer opportunities for resident independence due to changes in residency regulations, medical–legal concerns, and financial incentives. A survey study was conducted to assess perceived autonomy and preparedness during plastic surgery residency training and to assess factors affecting autonomy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“… 60 However, there are multiple studies indicating that surgical graduates feel variably prepared for independent professional practice. 61 , 62 , 63 , 64 , 65 Concerns regarding proficiency have linked to increased interest in post-residency clinical fellowships. 65 , 66 Additional operative exposure in a quality teaching environment is inherently beneficial for trainees, and the perceived disruption and impact of the coronavirus pandemic on clinical training and surgeon development, as highlighted in the aforementioned survey-based and qualitative studies of surgical residents, 31 , 33 , 34 , 35 , 37 , 38 , 40 , 41 underscores the extent to which trainees desire operative experience and hands-on training.…”
Section: Discussionmentioning
confidence: 99%
“… 60 However, there are multiple studies indicating that surgical graduates feel variably prepared for independent professional practice. 61 , 62 , 63 , 64 , 65 Concerns regarding proficiency have linked to increased interest in post-residency clinical fellowships. 65 , 66 Additional operative exposure in a quality teaching environment is inherently beneficial for trainees, and the perceived disruption and impact of the coronavirus pandemic on clinical training and surgeon development, as highlighted in the aforementioned survey-based and qualitative studies of surgical residents, 31 , 33 , 34 , 35 , 37 , 38 , 40 , 41 underscores the extent to which trainees desire operative experience and hands-on training.…”
Section: Discussionmentioning
confidence: 99%
“…According to a 2020 survey of plastic surgery residents and faculty, only 15.1% of residents strongly agreed that they were given enough autonomy during residency to practice in pediatrics/craniofacial surgery. 11 In the same study, attendings reported that the most significant factor associated with reduced resident autonomy was concern for patient outcomes, a concern which is likely even more pronounced when operating on children. It behooves program directors to regularly evaluate the relative exposure of residents to different subspecialties to allow for the development of interest in academically focused subspecialties, and craniofacial surgeons to routinely consider the extent of resident participation in their cases.…”
Section: Discussionmentioning
confidence: 97%
“…Exposure to craniofacial surgery and pediatric plastic surgery may be more challenging to obtain during residency than other areas of plastic surgery, both due to limited rotations and operative experience during rotations. According to a 2020 survey of plastic surgery residents and faculty, only 15.1% of residents strongly agreed that they were given enough autonomy during residency to practice in pediatrics/craniofacial surgery 11. In the same study, attendings reported that the most significant factor associated with reduced resident autonomy was concern for patient outcomes, a concern which is likely even more pronounced when operating on children.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by studies that have shown a significant association of lower case volume, or perception thereof, with lower self-reported competence, confidence, and preparedness in those procedures. 11,12 Amidst the backdrop of an increasing movement in both the United States and Canada advocating for a transition toward competencybased standards in plastic surgery GME, there is a real need for effective tools to directly assess technical surgical skills. 13,14 Although a number of such tools exist, the utility of many is hampered by factors such as unestablished validity, reliability, and transferability to clinical practice, as well as high barriers to implementation.…”
Section: Introductionmentioning
confidence: 99%